Inequality in Urban Infrastructure Accessibility to Slum Settlements: A Case Study of Bangkok Metropolitan - Denpaiboon, Chaweewan; Selanon, Pattamon; Denpaiboon, Krittaphas (Thai Journal of East Asian Studies, 2019)
Typically, accessibility of people with low-income to public urban infrastructure is unfairly managed, and this tendency seems to be gradually higher in the future. Objectives of this study are: (a) to study relationship between pattern of the slum community and accessibility to urban infrastructure; (b) to design system of accessing public services for low income people based on housing problem; and (c) to provide recommendations for social justice policies to the relevant government agencies. The selected three study areas include of Bangkapi district, Bangkok, Klong Luang, Pathumthani and Bang Phli, Samut Prakarn. Methods of the study cover literature review and the research’s interview as well as a fieldwork observation. The questionnaire was used along with the statistical package Social Science (SPSS) to describe the phenomenon of residents’ attitudes and receiving services. In addition, Bangkok’s geographic information is used in the Urban Analysis Model, ArcGIS 10.4 and the ArcGIS Software with the Network Analyst Extension in order to evaluate the relationship between variables and accessibility to the urban infrastructure. The study also combines considerations of the city's access to services, using the Human Development Index (HDI), which is a measuring tool of the United Nations Development Programme (UNDP) in ability to access to city services. The results demonstrate that the urban poor have access to city services and housing, but there is a lack of stability and justification in typical slum areas. In addition, there are also problems of the location of the slum communities in Bangkok and city services as followings:Typically, accessibility of people with low-income to public urban infrastructure is unfairly managed, and this tendency seems to be gradually higher in the future. Objectives of this study are: (a) to study relationship between pattern of the slum community and accessibility to urban infrastructure; (b) to design system of accessing public services for low income people based on housing problem; and (c) to provide recommendations for social justice policies to the relevant government agencies. The selected three study areas include of Bangkapi district, Bangkok, Klong Luang, Pathumthani and Bang Phli, Samut Prakarn. Methods of the study cover literature review and the research’s interview as well as a fieldwork observation. The questionnaire was used along with the statistical package Social Science (SPSS) to describe the phenomenon of residents’ attitudes and receiving services. In addition, Bangkok’s geographic information is used in the Urban Analysis Model, ArcGIS 10.4 and the ArcGIS Software with the Network Analyst Extension in order to evaluate the relationship between variables and accessibility to the urban infrastructure. The study also combines considerations of the city's access to services, using the Human Development Index (HDI), which is a measuring tool of the United Nations Development Programme (UNDP) in ability to access to city services. The results demonstrate that the urban poor have access to city services and housing, but there is a lack of stability and justification in typical slum areas. In addition, there are also problems of the location of the slum communities in Bangkok and city services as followings: 1. Most slum communities are far from the public transportation routes. 2. In term of basic educational institution, people from slum communities within a 1,000-meter radius seems to be able to reach the service. However, most of the slums are located in a radius of more than 1,000 meters, where the number of access is limited. 3. In aspects of market and career sources, most slums are located in a radius of more than 1,000 meters.4. For department store and shopping malls in Bangkok, slum communities can catch within a 1,000-meter radius. Finally, the study shows measurement of access to basic infrastructure services with an analysis of the Human Development Index (HDI). Findings of the study reveal that accessibility to urban infrastructure and housing is in low level when compared with users’ satisfaction analysis, which is also low.